1998
DOI: 10.1177/000494419804200203
|View full text |Cite
|
Sign up to set email alerts
|

Lecturing Performance Appraisal Criteria: Staff and Student Differences

Abstract: T HE assessment of academic staff teaching performance is an area of considerable concern and debate. The questions revolve around what should be assessed and by whom. In this study. the ratings of academic staff and tertiary students in a new institution were compared on 21 criteria of lecturing. Analysis of variance demonstrated that the academics placed significantly greater importance than students on a range of performance criteria (e.g. non-sexist language. independent learning, challenging the world Vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…Given the current results, a complementary vision of activating teaching methods and lectures tends to be appropriate and effective, as advocated by the results of the present study, or as suggested by the findings of Chisholm, Dehoney, and Poirier (1996), Michel (2001), Richardson and Birge (1995), and Woo and Kimmick (2000). In fact, from the students' perspective, the active nature of the teaching methods is not the primary feature that constitutes good teaching, but rather the criteria: pace of instruction and clarity (Fisher, Alder, & Avasalu, 1998). Interestingly, another often observed routine to explain negative results of the promising constructivist theory and its applications is to attribute these results to students' adaptation difficulties in the transition from traditional lectures to activating, independent learning/teaching settings (Novak, Shah, Candidate, Wilson, Lawson, & Salzman, 2006;Salamonson & Lantz, 2005;Vermetten, Vermunt, & Lodewijks, 2002).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Given the current results, a complementary vision of activating teaching methods and lectures tends to be appropriate and effective, as advocated by the results of the present study, or as suggested by the findings of Chisholm, Dehoney, and Poirier (1996), Michel (2001), Richardson and Birge (1995), and Woo and Kimmick (2000). In fact, from the students' perspective, the active nature of the teaching methods is not the primary feature that constitutes good teaching, but rather the criteria: pace of instruction and clarity (Fisher, Alder, & Avasalu, 1998). Interestingly, another often observed routine to explain negative results of the promising constructivist theory and its applications is to attribute these results to students' adaptation difficulties in the transition from traditional lectures to activating, independent learning/teaching settings (Novak, Shah, Candidate, Wilson, Lawson, & Salzman, 2006;Salamonson & Lantz, 2005;Vermetten, Vermunt, & Lodewijks, 2002).…”
Section: Discussionsupporting
confidence: 53%
“…These were 'build skills of self-learning', 'promote student interest in independent learning' and 'create an atmosphere for discussion'. These differences in perceptions of staff and students are mirrored by Fisher, Alder, and Avasalu (1998), Liow, Betts, and Kok Leong Lit (1993) and Trigwell, Prosser, and Waterhouse (1999) and could cause unexpected learning outcomes for students. Delucchi's (2000) results suggest that students who rate their instructor high in likeability reward that instructor with high ratings in overall teaching ability.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible interpretation is that students and staff hold quite different understandings of what good teaching is, with staff focusing on challenging students and developing independent learners, while students focus on more immediate or instrumental concerns about instruction (Fisher et al, 1998). Similarly, Clarke (1998) concluded that students' perceptions of what helps or hinders their learning are more congruent with a transmission model of teaching than a constructivist model and Crawford (1992) interpreted staff and students' different ways of understanding according to Perry's (1970) levels of intellectual and ethical development.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Similarly, Clarke (1998) concluded that students' perceptions of what helps or hinders their learning are more congruent with a transmission model of teaching than a constructivist model and Crawford (1992) interpreted staff and students' different ways of understanding according to Perry's (1970) levels of intellectual and ethical development. Fisher et al (1998) suggest that these differences may be due to the different roles played by each group-students as consumers and staff as providers of education, their experience in higher education, or their perceptions of the purpose and goals of higher education.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Furthermore, if Saroyan and Snell's framework is somewhat teacher-centred, Fisher et al (1998) provide a more balanced treatment. Twenty-one lecturing criteria were used as shown below (Note: the criteria are reorganised by the author into four aspects):…”
Section: Clarity: Claritymentioning
confidence: 99%